Investasi Sumber Daya Manusia dan Pengembangannya - Marifa Ayu Kencana (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2005)
Like in business sector, investment is also required in human resource through education and training. The basic assumption of the theory of human resource investment is that education and training will improve knowledge, skills and working productivity of the employees so that they will get appropriate compensation throughout their career. The success of all efforts to improve the quality of human resource really depends on the success of human resource investment. Therefore, in carrying out human resource investment, it is necessary to pay attention to the plan and strategy which are going to be delivered. Human resource investment will hopefully develop the characteristic of employees who are creative, adaptive, innovative, and responsible.